Kesetaraan Gender Dalam Perspektif Hukum Islam - Wati, Rahma; Aswen, Latif (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Gender is a cultural concept that seeks to make a difference in terms of roles, behaviors, mentality, and emotional characteristics between men and women that exist in society. The writing of this paper aims for every human being to get equal, fair, and equitable treatment in his daily life in terms of any aspect. In this study, the author used the method of theoretical studies, taking information through the process of reading, recording, collecting information from various sources such as books, journals, and various other references which are then used as a reference and reviewing theoretical studies. In Islam, several leadership principles are known, namely: responsibility, tawhid, deliberation, and fairness. In the perspective of gender equality, there is a belief that the Islamic religion does not lay between the rights and obligations that exist in the human anatomy in the opposite position, all of them are equal in the eyes of Islam. Islam views the two types as equal without looking at anyone. And the Qur'an has detailed the principles of gender equality in Islam including: equalizing the position of men and women as servants of Allah and equally as Caliphs on earth.